Multi-isotope constraints on biogeochemical processes during bank filtration: A case study of the Liao River, Northeast China. (November 2020) - Bai, Jing; Su, Xiaosi; Wang, Jiamei; Lyu, Hang; Gao, Ruimin; Lu, Shuai
Abstract: Significant physical, chemical and biological gradients between river water and groundwater will result in complicated biogeochemical reactions during riverbank infiltration (RBF), which can trigger release of toxic and/or harmful heavy metals/metalloids such as arsenic from the aqueous medium into groundwater and threaten the groundwater quality. It is crucial to understand these biogeochemical processes during RBF by effective tracing methods. In this study, a typical RBF site along Liao River in Northeast China was selected as case study area and multi-isotopes (such as δ 13 C, δ 34 S, δ 57 Fe and δ 56 Fe) coupled with hydrochemistry were used to trace the main biogeochemical processes during RBF. The research results shows that carbon, iron and sulfur isotopes act as good indicators of biogeochemical processes during river water infiltration. Organic carbon that drives biogeochemical processes comes primarily from dissolved organic carbon and sedimentary organic carbon. 34 S enrichment in groundwater SO4 2− quantified sulfate consumption with the enrichment factor of −13.86‰. Different 56 Fe variation types signify three pathways of iron cycling (microbial mediated reduction of Fe oxides/hydroxides, formation of Fe-sulfides and re-adsorption of Fe(II) into iron oxide minerals) were deduced in the groundwater. Highlights: Joint use of δ 13 C, δ 34 S and δ 57 Fe and δ 56 Fe isotopes and hydrochemistry to trace the main biogeochemical processes during river bank infiltration (RBF). Reveal sources of organic matter, sulfate and iron, and roles of sulfur and iron cycling in iron mobility. Provide significant insight for the development of sustainable groundwater resource uses.